Development and Validation of an Analytical RP-HPLC Method for Simultaneous Estimation of Losartan and its Active Metabolite (EXP-3174) in Isolated Perfused Rat Liver - Toolabi, Mahsa; Ramezankhani, Reyhaneh; Rahbar, Nadereh; Dibaei, Maryam; Foroumadi, Alireza; Lavasani, Hoda; Kazemi, Vida; Rouini, Mohammadreza (Current Pharmaceutical Analysis, 2023)
Background: The liver perfusion method is frequently used in drug pharmacokinetic studies and the various effects of drugs on liver tissue. The aim of this study was to establish and validate an analytical method using high-performance liquid chromatography to determine the simultaneous concentration of losartan and its active metabolite, EXP-3174, in an isolated perfused rat liver study.Method: An HPLC system with isocratic mode was used. Various chromatographic parameters were adjusted to develop and validate a method for determination of losartan and its active metabolite in liver perfusion media.Results: In this study, losartan and its active metabolite, EXP-3174, were separated using a C18 stationary phase, a mobile phase consisting of acetonitrile: phosphate buffer at a flow rate of 1 mL.min-1, and UV detection at 254 nm. Retention times for losartan and the metabolite were 10 and 16 minutes, respectively. Linearity from 25-250 ng.ml-1 was validated with acceptable accuracy and precision. The LOD and LOQ for losartan were 7.0 and 21.1 ng.ml-1, respectively. The LOD and LOQ for metabolite were 7.4 and 22.4 ng.ml-1, respectively. ChromGate® software was used to acquire and process the data.Conclusions: The optimized and validated technique was effectively used to analyze losartan and its active metabolite in isolated perfused rat liver.
Keywords: metabolism